Prevalence and associated factors of obesity and overweight in Chinese patients with bipolar disorder - Yi, Wenying; Wu, Haibo; Li, Ruikeng; Li, Haijing; Song, Zhen; She, Shenglin; Zheng, Yingjun (Frontiers in Psychiatry, 2022)
Object: Despite abundant literature demonstrating a high prevalence of obesity and overweight in people with bipolar disorder (BD), little is known about this topic in China. Therefore, we assessed the prevalence and associated factors of obesity and overweight among inpatients with BD in our hospital, one of the largest public psychiatric hospitals in China. Methods: In this retrospective, cross-sectional study, 1169 inpatients ≥ 18 years with BD during 2019 were included. Obesity was defined as having a BMI ≥ 25 kg/m2, and overweight was defined as having a BMI from 23 kg/m2 to less than 25 kg/m2. Binary logistic regression analysis was performed to identify factors associated with obesity and overweight. Results: The prevalence of obesity and overweight was 21.0% and 32.2% in patients with BD, respectively. Compared to patients with overweight and normal weight, patients with obesity were older, had a longer duration of BD and a longer length of hospital stay, had a higher prevalence of diabetes and hypertension, and had a higher level of all metabolic indices, except for HDL cholesterol. Binary logistic regression analysis showed that duration of BD, uric acid, alanine aminotransferase (ALT), triglyceride, and LDL cholesterol were significantly associated with obesity, and male sex and uric acid level were significantly associated with overweight (p < 0.05). Conclusions: Obesity and overweight were fairly prevalent in Chinese BD patients, and several factors were related to obesity and overweight. The results of the present study call for the need to implement early screening, prevention and interventions for obesity and overweight in patients with BD in China.